Investigating the thermal physiology of Critically Endangered North Atlantic right whales Eubalaena glacialis via aerial infrared thermography - GL Lonati; DP Zitterbart; CA Miller; P Corkeron; CT Murphy; MJ Moore (Endangered Species Research, 2022)
The Critically Endangered status of North Atlantic right whales Eubalaena glacialis (NARWs) warrants the development of new, less invasive technology to monitor the health of individuals. Combined with advancements in remotely piloted aircraft systems (RPAS, commonly ‘drones’), infrared thermography (IRT) is being increasingly used to detect and count marine mammals and study their physiology. We conducted RPAS-based IRT over NARWs in Cape Cod Bay, MA, USA, in 2017 and 2018. Observations demonstrated 3 particularly useful applications of RPAS-based IRT to study large whales: (1) exploring patterns of cranial heat loss and providing insight into the physiological mechanisms that produce these patterns; (2) tracking subsurface individuals in real-time (depending on the thermal stratification of the water column) using cold surface water anomalies resulting from fluke upstrokes; and (3) detecting natural changes in superficial blood circulation or diagnosing pathology based on heat anomalies on post-cranial body surfaces. These qualitative applications present a new, important opportunity to study, monitor, and conserve large whales, particularly rare and at-risk species such as NARWs. Despite the challenges of using this technology in aquatic environments, the applications of RPAS-based IRT for monitoring the health and behavior of endangered marine mammals, including the collection of quantitative data on thermal physiology, will continue to diversify.